PENILAIAN INDEKS ANCAMAN KEKERINGAN DI KECAMATAN DEMPO TENGAH KOTA PAGARALAM MENGGUNAKAN GIS - Kharumia Pasmah; Fameira Dhiniati; Barrorotul Azizah (LPPM Sekolah Tinggi Teknologi Pagar Alam, 2022)
Drought is an event that has a direct impact on several important sectors in Indonesia, including agriculture, forestry, plantations, and water resources. Geographic Information System has been developed with various methods. In addition, identification of drought areas is also carried out using the Regulation of the Head of the National Disaster Management Agency (Perka BNPB) Number 02 of 2012 concerning guidelines for disaster risk assessment. Can identify vegetation density conditions, which can be identified using the NDVI (Normalized Difference Vegetation Index) transformation, while other parameters such as rainfall, cover, land, and soil type are physiographical conditions that affect drought.